FUNGSI AJUNG DALAM MASYARAKAT IRANUN DAERAH KOTA BELUD, SABAH - Amat, Asmiaty; Asnari Taim, Mohd (JURNAL MELAYU SEDUNIA, 2020)
Sabah is a state rich in ethnic diversity and cultural heritage. One of the ethnic groups rich in cultural heritage is the Iranun. The Iranuns are a minority community that is very similar to the Bajau ethnic group. Most Iranuns live in Kota Belud and Lahad Datu, as well as scattered around Kota Kinabalu. This study focuses on the relics of Iranun heritage known as ajung, which is a replica of a house decorated with various types of colored fabrics. Fieldwork, observations and interviews were conducted in Merabau village, Nanamun village and Rampayan Laut village in Kota Belud district. This study explains the function of ajung in the cultural life of the Iranun people. Findings show that the ajung is not just a replica of a house decorated with various types of decorations and colors, but the ajung has an important function in the life of the Iranun community, aside from being a reflection of their ethnic identity.